Implementasi Penegakan Hukum Lingkungan Dalam Meningkatkan Efektivitas Perlindungan Dan Pengelolaan Terhadap Lingkungan Hidup (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This article will discuss "Implementation of Environmental Law Enforcement in Improving the Effectiveness of Environmental Protection and Management". In this study, using qualitative methods with a literature study approach as a research method. The results in this study show that environmental law enforcement is crucial in ensuring effectiveness in environmental protection and management efforts. The success of Law Number 32 of 2009 depends on its implementation and enforcement. Law enforcement acts as a driver or driver for laws and regulations. Although still faced with various challenges in an effort to improve the effectiveness of environmental protection and management, There are also several factors and strategies that are expected to achieve these goals, including socioeconomic and political factors, legal factors, institutional factors, internal factors, special factors, individual officer factors, law enforcement factors, supporting facilities or facilities, community factors, and cultural factors. Then, some environmental law enforcement strategies such as strict law enforcement, Strengthening existing environmental regulations by developing new regulations that are more effective in overcoming environmental problems, providing training to law enforcement officials, applying innovative technology in environmental law monitoring and enforcement, and cooperation between the government, law enforcement agencies, civil society, and the private sector is a crucial aspect of environmental law enforcement strategies.